2023
DOI: 10.1186/s12905-023-02369-1
|View full text |Cite
|
Sign up to set email alerts
|

Mother’s perceptions and concerns over sharing sexual and reproductive health information with their adolescent daughters- A qualitative study among mothers of adolescent girls aged 14–19 years in the developing world, Sri Lanka

Abstract: Introduction Studies across the world have shown that parent-adolescent SRH communication can prevent unhealthy sexual and reproductive health (SRH) practices among adolescents and promote their sexual and reproductive health. Parents have the ability to provide individualized sex education to suit the needs of their children, their families, and societal values. The fact that children have more opportunities in the family, makes parent-based sexuality education of children a better approach to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This difference may be attributed to parents being uncomfortable or not discussing SRH with their children, a common problem in many developing countries. 6,9,10 A study in Nigeria showed that only 12.3% of parents discuss SRH matters with their adolescent girls, 17 while another done in Ethiopia revealed that 14.7% of the discussion was with mothers and 3.9% with fathers. 18 These low numbers seem to be more prevalent in less developed nations, yet they are the ones that grapple more with teenage pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference may be attributed to parents being uncomfortable or not discussing SRH with their children, a common problem in many developing countries. 6,9,10 A study in Nigeria showed that only 12.3% of parents discuss SRH matters with their adolescent girls, 17 while another done in Ethiopia revealed that 14.7% of the discussion was with mothers and 3.9% with fathers. 18 These low numbers seem to be more prevalent in less developed nations, yet they are the ones that grapple more with teenage pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, research indicates that parents often are ill-equipped to address SRH topics with their teenage children due to cultural norms, discomfort, lack of knowledge, or misconceptions surrounding SRHR. 6,9,10 These create a knowledge gap between parents and their children since children are left to explore SRH with minimum parental guidance. 9,10 Despite previous studies reporting the discrepancy in the intergenerational knowledge about SRHR, this has not yet been explored in Rwanda, where mothers are considered the epitome of knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation